Practical Salesforce.com Development Without Code: Customizing Salesforce on the Force.com Platform - Weinmeister, Philip (Springer, 2015)
Are you facing a challenging Salesforce.com problem--say, relating to automation, configuration, formulation, or reporting--that you can't quite crack? Or maybe you are hoping to infuse some creativity into your solution design strategy to solve problems faster or make solutions more efficient? Practical Salesforce.com Development Without Code shows you how to unlock the power of the Force.com platform to solve real business problems--and all without writing a line of code. Adhering to Salesforce.com's "clicks, not code" mantra, Salesforce.com expert Phil Weinmeister walks you through different business problems and identifies effective, creative--and proven--approaches to solutions using the platform's declarative framework.